2019
DOI: 10.1089/aid.2018.0252
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Translocation Is Associated with Immune Activation and Systemic Inflammation in Treated HIV

Abstract: The mechanisms causing HIV-associated immune activation remain incompletely understood. Alteration of intestinal integrity with subsequent translocation of bacterial products appears to play an important role; however, little is known about the impact of fungal translocation. We assessed the effect of fungal translocation and its association with immune activation in people living with HIV (PLWH) compared with uninfected controls. We measured serum levels of b-D-glucan (BDG) and anti-Saccharomyces cerevisiae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
2
27
2
Order By: Relevance
“…Similarly to LPS, BDG has been associated with inflammation and immune activation in PWH [12, 29, 32, 39, 40]. Contrary to previous reports, we failed to observe any association between BDG and markers of monocyte, T-cell activation, or systemic inflammation at any time point.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly to LPS, BDG has been associated with inflammation and immune activation in PWH [12, 29, 32, 39, 40]. Contrary to previous reports, we failed to observe any association between BDG and markers of monocyte, T-cell activation, or systemic inflammation at any time point.…”
Section: Discussioncontrasting
confidence: 99%
“…Markers such as β-D-glucan (BDG), a polysaccharide cell wall component of most fungal species, is known to be highly immunogenic, stimulating macrophages, neutrophils, and T cells and leading to release of pro-inflammatory cytokines such as interleukin (IL)-8 and tumor necrosis factor α [10, 11]. We have previously observed that markers of fungal translocation are associated with immune activation and systemic inflammation in virally suppressed PWH [12].…”
mentioning
confidence: 99%
“…The results reported by Mehraj et al complement the findings of that case-control study by identifying early ART as an effective intervention to cease the increase of βDG levels. The findings by Mehraj et al can be also seen as being in line with findings from other recent studies in which it was found that circulating βDG levels in PLWH on ART correlated with other markers of immune activation [12,13], systemic inflammation [13,14], and microbial translocation, including Lactobacillales proportions in the gut microbiome [6], and that elevated βDG levels were associated with neurocognitive and cardiovascular non-AIDS events [15,16].…”
supporting
confidence: 86%
“…Measurement of microbial translocation plasma markers have been frequently performed in studies evaluating therapeutic interventions and assessing the risk of developing non-AIDS co-morbidities [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Circulating levels of lipopolysaccharide (LPS) are commonly measured to assess the level of bacterial translocation.…”
Section: Introductionmentioning
confidence: 99%